The value of dicalcium phosphate, Vitamin A, and grinding sorghum grain for calves fed prairie hay - Smith, E.F.; Richardson, D.; Kramer, J.E.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The 60 steer and heifer calves, six steers and four heifers per lot, used in this experiment, were good to choice grade Herefords from near Fort Davis, Texas, and were assigned on a random-weight basis to their treatments. All lots received all the prairie hay they would consume, 4 pounds of sorghum grain, and 1 pound of soybean meal per head daily. Where Vitamin A (10,000 I.U. daily) and dicalcium phosphate (0.1 pound per head daily) were fed they were mixed with the soybean meal. In the lots fed ground sorghum grain, it was ground medium fine.
Keywords: Beef; Vitamin A; Sorghum; Dicalcium phosphate